Meta-analysis of BACE1 gene rs638405 polymorphism and the risk of Alzheimer's disease in Caucasion and Asian population. (11th March 2016) - Yu, Minhua; Liu, Yue; Shen, Jun; Lv, Dongwei; Zhang, Junjian
Highlights: This is the latest meta-analysis to discuss about the risk of AD and SNP rs638405 polymorphism of BACE1 gene. The strengths of our analysis include the strict criteria of eligible studies and general report by additional subgroup analysis. We demonstrated the SNP rs638405 polymorphism of BACE1 gene displayed significant association with AD both in Asian population, Caucasion population and overall population. Abstract: Recent studies showed the β-site amyloid precursor protein cleaving enzyme (BACE) is associated with Alzheimer's disease (AD). However, studies investigating the association of single-nucleotide polymorphism (SNP) in exon 5 of BACE1 (rs638405, C786G, Val262) with AD are controversial. Therefore we conducted this meta-analysis to clarify the association. Relevant studies were identified on PubMed, Cochrane library and CNKI from established through July 2015 according to the inclusion criteria. Odds ratios (ORs) with 95% confidence intervals (CIs) and five genetic models were applied to assess the association. A total of 13 studies composed of 2538 AD patients and 3020 controls were included in this study. Significant association of SNP rs638405 with AD was found in overall population among allelic genetic model (G vs. C: OR = 1.11, 95%CI = 1.02–1.20, P = 0.01), codominant genetic model (GG vs. CC: OR = 1.22, 95%CI = 1.04–1.44, P = 0.02) and recessive genetic model (GG vs. GC+ CC: OR = 1.25, 95%CI = 1.10–1.42, P = 0.0008). Besides, subgroup analysis indicated significant association among Asian population (allelic genetic model, G vs. C, OR = 1.18, 95%CI = 1.04–1.34, P = 0.01; codominant genetic model, GG vs. CC, OR = 1.43, 95%CI = 1.08–1.89, P = 0.01 and recessive genetic model, GG vs. GC+ CC, OR = 1.40, 95%CI = 1.09–1.78, P = 0.008) and Caucasion population (recessive genetic model, GG vs. GC+ CC, OR = 1.20, 95%CI = 1.02–1.39, P = 0.02). Our analysis demonstrated that GG genotype and G allele of BACE1 gene rs638405 probably increase the risk of AD.